Optical and electrical properties of the PLT films with various compositions deposited by sol-gel process - Yoon, YS; Jung, HJ (SPRINGER, 1999)
In order to study optical and electrical properties of (Pb1-xLax)TiO3 (PLT) films with varying La concentration, the PLT films were deposited by sol-gel process. X-ray diffraction revealed that a pseudocubic phase of the PLT film became dominant with increasing La concentration due to decrease of lattice constant of c-axis. Three-dimensional atomic force microscopy images showed that the grain size and root mean square surface roughness decreased by addition of La. The optical band gap of the PLT films became wider when Pb was substituted with La. The addition of La increased the transparency of the PbTiO3 film and shifted the threshold for initiation of absorption to shorter wavelength. Hysteresis loops of the PLT films showed that remanent polarization and coercive field decreased with increasing La concentration. In addition, we modified the surface of the PLT film with La concentration of 5% using a keV oxygen ion beam at different doses. The optical band gap of the PLT film was changed by the oxygen ion beam irradiation although the XRD patterns and the transmittance values were not significantly changed. In measuring AFM images of the surface of modified PLT film, significant changes of the grain shape and size were not found. Moreover, polarization and dielectric constant were not changed after oxygen ion irradiation. These results suggested that addition of La could affect the optical and electrical properties of the PbTiO3 and PLT films and that surface modification by oxygen ion beam modification with 1 keV energy can change the surface property but not bulk property.
Keywords: TITANATE THIN-FILMS; FABRICATION; OXIDE